(3fHPI aj CfSGH GdQhe hef hGdGges - (3YHO GdhGMO Hf EHQGgje GdMSjfj GdTGaYj, GHf Gdabjg,J (B636 (3g` s
(3BNQgG (B:s
(3bGd GdENHGQjhf (B: (3Ef YjUh Hf ESMGb deG aGQb jYbhH NQL Edi GdYOhI hgj eSGcf GdQhe GdChd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B174s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B165 s
Keywords: (3GdJGQjNs